CREB function is required for normal thymic cellularity and post‐irradiation recovery - Baumann, Sven; Kyewski, Bruno; Schmid, Wolfgang; Krammer, Peter H.; Schütz, Günther (European journal of immunology, 2004)
Recent generation of genetically modified Creb1 mutant mice has revealed an important role for CREB (cAMP responsive element binding protein) and the related proteins CREM (cAMP responsive element mo...